Solitary Crossed Renal Ectopia with Vesicoureteral Reflux - Fallahzadeh, Mohammad Amin; Derakhshan, Ali; Fallahzadeh, Mohammad Kazem; Ghasemov, Masroor; Falahzadeh, Mohammad Hossein (Journal of Pediatric Nephrology, 2014)
<!–[if gte mso 9]> <![endif]–> <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Solitary crossed renal ectopia is a rare anomaly of the urinary tract. This anomaly is often diagnosed incidentally when patients are being evaluated for other associated findings including genitourinary, cardiovascular, hematological or vertebral abnormalities. We report a boy with solitary crossed renal ectopia that was considered a solitary normal positioning kidney by ultrasonography and dimercaptosuccinic acid scan. However, voiding cystourethrogram revealed vesicoureteral reflux and crossed ectopia. Therefore, in any normal appearing solitary kidney, crossed ectopia may be a possible finding. <span style="font-size: 10.0pt; line-height: 115%; font-family: ’Cambria’,’serif’; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: Arial; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Keywords:<span style="font-size: 10.0pt; line-height: 115%; font-family: ’Cambria’,’serif’; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> Ectopic<span style="font-size: 10.0pt; line-height: 115%; font-family: ’Cambria’,’serif’; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Kidney; Vesico-Ureteral Reflux<span style="font-size: 10.0pt; line-height: 115%; font-family: ’Cambria’,’serif’; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: Arial; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">; Ureter.